Postoperative Imaging After Lobectomy: Predicting the Displacement and Change in Orientation of Nonresected Lung Nodules. Issue 4 (July 2019) - Digumarthy, Subba R.; Shukla, Priya K.; Mendoza, Dexter P.; Guo, Lancia; Chretien, Yves R.; Shepard, Jo-Anne O.; Kalra, Mannudeep K.
Abstract : Objectives: The objective of this study was to determine the effect of a lobectomy to the location and orientation of nonresected lung nodule and its corresponding airway. Methods: We reviewed preoperative and postoperative computed tomography of patients who underwent lobectomies and have a separate nonresected nodule in the ipsilateral lung. Displacement of the nonresected nodule and angulation of its corresponding segmental bronchus were measured. Results: Fifty nodules from 40 patients (30 females, 10 male; mean ± SD age, 67 ± 7 years) were assessed. Nodules are displaced clockwise after right upper, right middle, and left lower lobectomies and counterclockwise after right lower and left upper lobectomies. Displacement of the remaining nodules was greater in the craniocaudal plane, followed by anteroposterior and transverses planes (mean, 3.7, 2.5, and 1.9 cm, respectively). Conclusions: Remaining ipsilateral nodules and their associated segmental airways are displaced in a predictable fashion after lobectomy. This may help in the assessment of follow-up imaging.